Kinetics of the mechanochemical transformations in the “glycine - oxalic acid dihydrate” system revisited: The role of water - Losev, Evgeniy; Kalinina, Polina; Golomolzin, Artem; Kolesnikova, Viktoria; Boldyreva, Elena (Frontiers in Chemistry, 2025)
Introduction: Kinetics of the mechanochemical transformations in the “glycine–oxalic acid dihydrate” system were revisited, in order to compare the results obtained for ball milling of the same reactants in different ball-milling devices.Methods: The results obtained in a commercial vibrational mill NARVA Vibrator DDR-GM9458 (ex situ study, this work) were compared with the previously published studies: ex situ in a home-made restricted-impact device and in situ in a Retsch MM400 vibrational mill.Results: We studied the effect of various factors on the mechanochemical transformations in this system under different conditions, such as the air humidity, the effect of the frequency of mechanical pulses on the existence of the induction period, the effect of the starting glycine polymorph on the duration of the induction period in case of a high-frequency vibrational ball milling, or the formation of G2O and GO as two competing products, the former dominating at the early stage of treatment as a “kinetic”, faster crystallizing phase, and the latter formed as the only final thermodynamically stable product after a prolonged treatment.Discussion: The abovementioned results were interpreted consistently considering the possibility that water released from oxalic acid crystal hydrate may have a significant effect on the mechanochemical transformations, even though it does not enter crystal structures of bis-glycinium oxalate (G2O) and glycinium semioxalate (GO) products.